From up on Poppy Hill [videorecording (Blu-Ray + DVD)] - Miyazaki, Hayao, 1941-; Niwa, Keiko; Takebe, Satoshi, 1957-; Okui, Atsushi; Takahashi, Chizuru (Distributed in the U.S. by Cinedigm Entertainment, 2013)
"Yokohama, 1963. Japan is picking itself up from the devastation of World War II and preparing to host the Olympics. Against this backdrop of hope and change, a friendship begins to blossom between high school students Umi ... and Shun ... but a buried secret from their past emerges to cast a shadow on the future and pull them apart"--Container.